Insight Into the Function of RIPK4 in Keratinocyte Differentiation and Carcinogenesis - Xu, Jing; Wei, Qichun; He, Zhixing (Frontiers in Oncology, 2020)
The receptor-interacting protein kinase 4 (RIPK4), a member of the RIPK family, was originally described as an interaction partner of protein kinase C (PKC) β and PKCδ. RIPK4 is identified as a key regulator of keratinocyte differentiation, cutaneous inflammation, and cutaneous wound repair. The mechanism by which RIPK4 integrates upstream signals to initiate specific responses remains elusive. Previous studies have indicated that RIPK4 can regulate several signaling pathways, including the NF-κB, Wnt/β-catenin, and RAF/MEK/ERK pathways, etc. Furthermore, RIPK4-related biological signaling pathways interact with each other to form a complex network. Mounting evidence suggests that RIPK4 is aberrantly expressed in various kinds of cancers. In several types of squamous cell carcinoma (SCC), the mutations that drive aggressive SCC have been found in RIPK4. In addition, the function of RIPK4 in carcinogenesis is probably tissue-specific, since RIPK4 can play a dual role as both a tumor promoter and a tumor suppressor in different tumor types. Therefore, RIPK4 may represent as an independent prognostic factor and a promising novel therapeutic target, which can be used to identify the risks of patients and guide personalized treatments. In future, RIPK4-interacting pathways and precise molecular targets need to be investigated in order to further elucidate the mechanisms underlying epidermal differentiation and carcinogenesis.